The effectiveness of pocket book of healthy lifestyle for the elderly during covid-19 pandemic at the Ambon city health center - Pudyastuti, Rita Rena; Kariyadi, Kariyadi; Setyowati, Sri Eny; Saleh Dunggio, Abdul Rivai (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
During the Covid-19 pandemic that occurred from March 2020 until now, the elderly is very vulnerable to transmission of the Covid-19 virus because their immune system has begun to decrease. This study aims to determine changes in the knowledge of the elderly before and after being given the elderly healthy pocket book. The research method uses a one group pre-posttest design. The product produced from this research is a healthy pocket book for the elderly that can be used as a guide for the elderly in maintaining health to avoid transmission of Covid-19. To find out the effectiveness of the pocket book to be produced, measurements were made of the knowledge of the elderly before and after being given the pocket book to 50 respondents using incidental sampling, namely the elderly who were found when the elderly visited the Rumah Tiga Health Center. The results showed that that pocket books for healthy lifestyles for the elderly during the Covid-19 pandemic were quite effective. It is hoped that the results of this study can be useful for the elderly and can also play a role in controlling the transmission of the Covid-19 virus in Maluku.